Rural commercial bank's efficiency on supporting rural revitalization in China: do leverage implementation and green finance matter? - Li, Yue; Mohd Ashhari, Zariyawati; Ab Razak, Nazrul Hisyam; Soh, Wei Ni; Tang, Xianghua; Kang, Kuan (John Wiley and Sons, 2025)
This paper provides an in-depth examination of the role of rural financial institutions in rural development under deleveraging and greening externalities orientating China's economic transition. Specifically, we examine the impacts of leverage implementation and green finance on the multi-dimensional efficiency (i.e., financial, social and comprehensive) of rural commercial banks (RCBs) in the following distinct ways. First, we account for the symmetric and asymmetric relationships between leverage and efficiency through a comparable analysis of using the ARDL model and the NARDL model, which follow dynamic heterogeneous panel data modelling by Shin et al. Second, we investigate the relationship between green finance and efficiency in an identical manner. Third, in order to capture potential nonlinearity, we quantify macroprudential green finance to ascertain its threshold effect on the leverage-efficiency association by using the Hansen model. Our results depict that RCBs' efficiency, regardless of the dimensions involved, responds asymmetrically to changes in their leverage in both the long and short runs, while their asymmetric response to changes in green finance occurs solely in the long run. This finding is further corroborated by intuitive results of the cumulative sum of squares simulation and consolidates the observed financial accelerator effects in symmetric relationships. Additionally, the threshold role of macroprudential green finance triggers nonlinearity in associations of leverage with social and comprehensive efficiency. This finding suggests that, in light of the development of green finance, minor adjustments to macroprudential regulation below the threshold can facilitate micro prudence for RCBs' deleveraging.